Broccoli sprouts modulate the effect of carbohydrates on Drosophila pupation: acceleration on high-sugar diets, delay on low-sugar diets - Ivanochko, Marian; Kharuk, Sviatoslav; Lylyk, Maria; Gospodaryov, Dmytro (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2025)
Diet-induced obesity has become a global health concern, driving the search for effective preventive measures and functional food interventions. This study evaluates the potential of broccoli sprouts as a functional supplement to counteract the effects of an obesogenic diet in Drosophila melanogaster, a widely accepted model organism for studying metabolic diseases. The research examined the influence of broccoli sprout supplementation on larval pupation rates, adult fly body mass, and the content of proteins and triacylglycerols (TAGs) in adult flies. Larvae were fed diets with varying sucrose concentrations, with or without broccoli sprouts. Results showed that broccoli sprouts independently slowed larval development, irrespective of sucrose-induced delays. While no significant effects on body mass were observed in adult males, female flies exhibited reduced body mass in some broccoli-supplemented groups. Metabolically, TAG levels and protein content varied across diets, with high sucrose diets generally increasing TAG levels. However, broccoli sprouts mitigated some adverse metabolic changes, particularly in male flies on high-sucrose diets. These findings suggest that broccoli sprouts impact developmental timing in Drosophila and highlight their potential modulatory effects on metabolic markers associated with diet-induced obesity. The study underscores the need for further investigation into optimal doses and the underlying mechanisms of broccoli's bioactive compounds in mitigating obesity-related metabolic alterations. Future research should also address parameters such as food intake, survival rates, and oxidative stress markers to understand the broader implications of broccoli supplementation better.